Serialized China standard metro train electrical system - TANG Feilong; LAI Senhua; YU Qingsong (机车电传动)
In view of the problems of low standardization, variety of spare parts and low intelligence of the electrical system of domestic rail transit vehicles, based on the principles of top-level design of the serialized China standard metro train, the technical application of the electrical system of the subway vehicle was investigated, and the application of the new technology on the subway vehicle was analyzed. The interface specification for the electrical system components of different models was formulated, and a unified standard for the function and performance of the electrical systems of different models was realized, the serialized China standard subway train electrical system platform has been developed, which realized the intelligence, configuration and functional performance upgrade of the electrical system. A safer, smarter and more energy-efficient electrical system platform can lay the foundation for the promotion and application of serialized standard metro train and the construction of smart urban rail.